Efektivitas Perencanaan dan Pengadaan Logistik Kesehatan dalam Menjamin Ketersediaan Obat di Puskesmas Medan Sunggal - Nanda Fadillah Darus; Supangge Tiara Aulia; Zulaila, Zulaila; Della Dwi Syahpira (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
This study aims to analyze the effectiveness of health logistics planning and procurement in ensuring drug availability at the Medan Sunggal Health Center. The availability of drugs that are timely and as needed is very important in supporting optimal health services. The method used in this research is descriptive qualitative with a case study approach. Data were collected through interviews, observations, and documentation related to the planning process and drug procurement. The results showed that although the planning system has followed standard procedures such as e-Planning and e-Logistics filling, there are still obstacles such as delays in distribution, discrepancies between planning and realization of needs, and limited human resources in monitoring. Efforts such as improved coordination with the Health Office and training of logistics officers are important to overcome these obstacles. With more effective logistics planning and procurement, drug availability can be better ensured and health services to the community will improve